Labour market policies for inclusiveness: A literature review with a gap analysis - Ekkehard Ernst; Rossana Merola; Jelena Reljic (International Labour Organization (ILO), 2022)
The COVID-19 pandemic triggered renewed interest in the use of different fiscal spending and transfer programmes to address the worsening conditions and deepening inequalities within the labour markets. This paper reviews the role of specific fiscal spending and transfer programmes in shaping labour market dynamics by disentangling different macroeconomic and microeconomic mechanisms. The paper presents the recent empirical evidence on the topic in an attempt to abstract several empirical regularities and identify research gaps. The analysis also highlights gaps in the literature and suggests how future research could fill these gaps.
Keywords: 330; labour contracts; labour standards; economic policy; labour administration; labour statistics